2019
DOI: 10.1152/physiol.00038.2018
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Exercise and Mitochondrial Biogenesis: Current Controversies and Future Research Directions

Abstract: It is well established that different types of exercise can provide a powerful stimulus for mitochondrial biogenesis. However, there are conflicting findings in the literature, and a consensus has not been reached regarding the efficacy of high-intensity exercise to promote mitochondrial biogenesis in humans. The purpose of this review is to examine current controversies in the field and to highlight some important methodological issues that need to be addressed to resolve existing conflicts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
125
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 107 publications
(135 citation statements)
references
References 137 publications
(151 reference statements)
2
125
0
Order By: Relevance
“…Therefore, biochemical measurements are often used as a surrogate of mitochondrial content (reviewed in more detail in Bishop et al . ). Due to its strong correlation with measurements of mitochondrial fractional area (as assessed by TEM) at rest (Larsen et al .…”
Section: Relationship Between Training Volume and Training‐induced Chmentioning
confidence: 99%
“…Therefore, biochemical measurements are often used as a surrogate of mitochondrial content (reviewed in more detail in Bishop et al . ). Due to its strong correlation with measurements of mitochondrial fractional area (as assessed by TEM) at rest (Larsen et al .…”
Section: Relationship Between Training Volume and Training‐induced Chmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] While these responses are affected by the nature of the exercise (eg, the exercise intensity 2,9,10 ), there is evidence substrate availability is also a potent modulator of this response. [1][2][3][4][5][6][7][8] While these responses are affected by the nature of the exercise (eg, the exercise intensity 2,9,10 ), there is evidence substrate availability is also a potent modulator of this response.…”
Section: Introductionmentioning
confidence: 99%
“…Endurance exercise is a powerful stimulus affecting cytoplasmic and nuclear proteins, and genes encoding mitochondrial proteins, with a subsequent increase in mitochondrial biogenesis (ie, the generation of new mitochondrial components leading to increased mitochondrial content and respiratory function). [1][2][3][4][5][6][7][8] While these responses are affected by the nature of the exercise (eg, the exercise intensity 2,9,10 ), there is evidence substrate availability is also a potent modulator of this response. [11][12][13][14] It has been hypothesized that initiating endurance exercise with low muscle glycogen stores (the so-called "train-low" approach) results in a greater increase in the content of nuclear proteins 15,16 and in the transcription of genes [17][18][19][20] associated with mitochondrial biogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to beginning this phase of the larger study, participants were familiarized with the 20k-TT, the GXT and the HIIE, and completed the normal volume training (NVT) phase (12 HIIT sessions in 4 weeks; Figure 1). It has been reported that the transcriptional response to the first session of exercise (first bout effect (4)) can differ significantly from the response to subsequent exercise sessions (4, 50, 55, 72). Thus, the NVT phase served not only to habituate participants to the rigors of twice-daily HIIT during the HVT phase, but also to eliminate possible biases brought about by the “first-bout” effect (4).…”
Section: Methodsmentioning
confidence: 99%